Thrombosis in Cancer Patients Treated with Hematopoietic Growth Factors - A Meta-Analysis - Barbul, T; Finazzi, G; Grassi, A; Marchioli, R (Thrombosis and Haemostasis, 1996)
Hematopoietic colony-stimulating factors (CSFs) are largely used in patients with cancer undergoing cytotoxic treatment to accelerate neutrophil recovery and decrease the incidence of febrile neutropenia. Clinical practice guidelines for their use have been recently established (1), taking into account clinical benefit, but also cost and toxicity. Vascular occlusions have been recently reported among the severe reactions associated with the use of CSFs, in anedoctal case reports (2, 3), consecutive case series (4) and randomized clinical trial (5, 6). However, the role of CSFs in the pathogenesis of thrombotic complications is difficult to ascertain, because pertinent data are scanty and widely distributed over a number of heterogenous investigations. We report here a systematic review of relevant articles, with the aims to estimate the prevalence of thrombosis associated with the use of CSFs and to assess if this rate is significantly higher than that observed in cancer patients not receiving CSFs.